Literature Review: The Role of Media in Integrated Marketing Communication (IMC) on Consumer Purchase Interest - Rahma, An Nisa Dian; Yudha, Angga Tinova; Sembiring, Putri Sosanti; Rizqiana, Dyah Seruni (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to examine the role of media in supporting Integrated Marketing Communication (IMC) in increasing consumer buying interest. The method used is a literature study with various academic sources and previous research reviewed related to consumer behavior, communication media, and IMC. The results of the study show that the media forms brand awareness, positive perceptions, and emotional relationships between customers and brands. The connection of messages across various media within the IMC framework has been shown to accelerate the customer's experience with the product, from the stage of knowing the product to making a purchase decision. Therefore, in contemporary marketing strategies, the strategic factors that increase purchase intention are good media selection, integration and management.